2023
DOI: 10.1021/acsnano.3c01960
|View full text |Cite
|
Sign up to set email alerts
|

MC1R Peptide Agonist Self-Assembles into a Hydrogel That Promotes Skin Pigmentation for Treating Vitiligo

Abstract: Vitiligo, a common skin disease that seriously affects 0.5−2.0% of the worldwide population, lacks approved therapeutics due to a wide range of adverse side effects. As a key regulator of skin pigmentation, MC1R may be an effective therapeutic target for vitiligo. Herein, we report an MC1R peptide agonist that directly self-assembles into nanofibrils that form a hydrogel matrix under normal physiological conditions. This hydrogel exhibits higher stability than free peptides, sustained release, rapid recovery f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, after taVNS, the MDA concentration significantly decreased, and SOD and CAT activities were restored ( p < 0.05). Oxidative stress can induce apoptosis of melanocytes in the skin, resulting in reduced tyrosinase synthesis in apoptotic melanocytes [ 21 , 22 ]. We measured the level of tyrosinase in mouse skin, and the results showed a significant reduction in tyrosinase content in the skin of vitiligo mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, after taVNS, the MDA concentration significantly decreased, and SOD and CAT activities were restored ( p < 0.05). Oxidative stress can induce apoptosis of melanocytes in the skin, resulting in reduced tyrosinase synthesis in apoptotic melanocytes [ 21 , 22 ]. We measured the level of tyrosinase in mouse skin, and the results showed a significant reduction in tyrosinase content in the skin of vitiligo mice.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments have shown that multiple cell lines can be cultured within the peptide hydrogel with high cell viability, enabling cells to grow into complex morphology. As a result, the peptide hydrogel developed shows great promise as a versatile tool for a variety of biomedical applications, including drug release, drug screening, and tissue engineering. , …”
Section: Discussionmentioning
confidence: 99%
“…Thus, MC1R emerges as a potential therapeutic target for vitiligo since MC1R plays a crucial role in regulating skin pigmentation. Recently, a novel MC1R peptide agonist is reported, and we will introduce it in the synthetic peptide modulators section [70].…”
Section: Melanomamentioning
confidence: 99%
“…Moreover, the peptide hydrogel shows potential for preventing UV-induced melanoma and other skin cancers. Consequently, Zhu et al suggest that this selective and potent MC1R agonist hydrogel presents an alternative for the treatment or prevention of skin pigmentation disorders such as EPP and melanoma [70].…”
Section: Peptide Agonist For Vitiligo Treatmentmentioning
confidence: 99%